Erosion Corrosion and Protection of Recycle System with Seawater - Xue Jin; Xue Kaijie; Lu Jianshu (MATEC Web of Conferences, 2016)
In order to investigate the corrosion of recycle system with seawater in rights of power plant, the erosion behavior and mechanism of erosion corrosion in this system constructed with several corrosionresistance alloys have been studied and tested in the condition of high speed fluid with a sand particles. Both special protection technologies and results, one designed by high temperature epoxy resin powder coating and another of the associating method of anode protection together with such same coating, have been discussed as well in this case.